Skull base osteomyelitis (SBO): a dreaded clinical entity - Khanum, Iffat; Kanwar, Dureshahwar; Habib, Kiren; Mubarak, Fatima (Journal of the Pakistan Medical Association, 2024)
Objectives: To identify the risk factors and clinical manifestations associated with skull base osteomyelitis. Method: The retrospective study was conducted at the Aga Khan University Hospital, Karachi, and comprised data from July 2013 to October 2020 related to adult patients of either who presented with base osteomyelitis. All relevant data was retrieved from hospital records. Data was analysed using SPSS 16. Results: Of the 56 patients with a mean age of 58.12±17.79 years, 39 (69.6%) were males. Diabetes was the most common comorbidity (n 39, 69.6%). The majority of patients had chronic sinusitis (n 34,60.7%) otitis media (n 20, 35.7%) or head and neck surgery (n 18, 32.1%) within the preceding 2 years. The mean duration between onset of symptoms and presentation to healthcare facility was 12±13.96 weeks. The most common presenting symptom was headache (n 38, 68%). The majority of patients (n 34 ,59.6 %) had fungal organisms isolated from tissue culture. Cranial nerve palsies were present in 44 (77%) patients. Out of 56 patients, 22(39.2%) were lost to follow and overall mortality was high (n 11, 19.6%). Sepsis was found to be associated with increased mortality (p=0.008). Conclusion: Skull base osteomyelitis was associated with significant morbidity and mortality, and posed significant diagnostic and therapeutic challenges. Key Words: Magnetic resonance imaging, Skull base, Infections, Osteomyelitis, Mortality.